2022
DOI: 10.1101/2022.10.17.512570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of multiple conformational states by combining sequence clustering with AlphaFold2

Abstract: AlphaFold2 (AF2) has revolutionized structural biology by accurately predicting single structures of proteins and protein-protein complexes. However, biological function is rooted in a protein's ability to sample different conformational substates, and disease-causing point mutations are often due to population changes of these substates. This has sparked immense interest in expanding AF2's capability to predict conformational substates. We demonstrate that clustering an input multiple sequence alignment (MSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(148 citation statements)
references
References 60 publications
4
143
0
1
Order By: Relevance
“…Predictions of fold-switchers have moderately reduced pLDDT versus single-fold proteins, but the pLDDTs are still substantially higher than for disordered proteins or disordered regions of specific proteins. Even more strikingly, Wayment-Steele and colleagues have shown that by clustering the sequences used by AlphaFold2, the algorithm can actually predict both folds in specific fold-switching systems 20 . This exciting result suggests that predictions of structural distributions may not be far off, as AlphaFold2 can already produce multiple correct structural outputs for the same protein.…”
Section: A Single Structure Cannot Capture Functional Motionmentioning
confidence: 99%
“…Predictions of fold-switchers have moderately reduced pLDDT versus single-fold proteins, but the pLDDTs are still substantially higher than for disordered proteins or disordered regions of specific proteins. Even more strikingly, Wayment-Steele and colleagues have shown that by clustering the sequences used by AlphaFold2, the algorithm can actually predict both folds in specific fold-switching systems 20 . This exciting result suggests that predictions of structural distributions may not be far off, as AlphaFold2 can already produce multiple correct structural outputs for the same protein.…”
Section: A Single Structure Cannot Capture Functional Motionmentioning
confidence: 99%
“…The model has been made available to the public with DeepMind’s official open-source implementation, which has been used to predict the structures of hundreds of millions of proteins (Tunyasuvunakool et al 2021, Varadi et al 2021, Callaway 2022). This implementation has enabled researchers to optimize AlphaFold2’s prediction procedure and user experience (Mirdita, Schütze, et al 2022) and to employ it as a module within novel algorithms, including ones for protein complex prediction (Baek 2021), peptide-protein interactions (Tsaban et al 2022), structure ranking (Roney and Ovchinnikov 2022), and more ( e.g ., Baltzis et al 2022, Bryant et al 2022, Wayment-Steele et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently different works showed results of increased capacity of AF2 to reproduce protein conformational diversity using alignment subsampling (Del Alamo et al, 2022; Wayment-Steele et al, 2022). In an attempt to increase the information of evolutionary trajectories in the input used by AF2, we used ancestral reconstruction prediction (Joy et al, 2016).…”
Section: Resultsmentioning
confidence: 99%